PENGARUH YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERBANKAN - Rivaldi Arie Maulana; Widyasari Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this research is to find out if there is a positive and significant relationship between Dividend Policy, Profitability, Liquidity, and Capital Structure on Firm value. This research was conducted by surveying banking sector companies that have been listed on the Indonesia Stock Exchange (IDX) in the period 2016-2018. Out of 45 companies listed on the Indonesia Stock Exchange (IDX), there are 14 companies that meet the sample criteria for research. All data obtained is processed by using e-views 11 software. After the research, obtaining results is a positive and insignificant relationship between dividend policy, profitability, liquidity, and capital structure on Firm value.